Osteoarthritis and functional disability: results of a cross sectional study among primary care patients in Germany - Rosemann, Thomas (BioMed Central, 2007)
BACKGROUND: The aim of the study was to determine factors associated with functional disability in patients with OA. METHODS: 1250 questionnaires were distributed to OA outpatients from 75 general practices; 1021 (81.6%) were returned. Questionnaires included sociodemographic data, the short form of the Arthritis Impact Measurement Scale (AIMS2-SF), and the Patient Health Questionnaire (PHQ-9) to assess concomitant depression. A hierarchical stepwise multiple regression analysis with the AIMS2-SF dimension "lower body" as dependent was performed. RESULTS: Main factors associated with functional disability were depression symptoms, as reflected in a high score of the PHQ-9 (beta = 0.446; p < 0.0009), pain as reflected in the AIMS2-SF symptom scale (beta = 0.412; p = 0.001), and few social contacts (beta = 0.201; p < 0.042). A high body mass index was associated with lower functional ability (beta = 0.332; p = 0.005) whereas a higher educational level (beta = -0.279; p = 0.029) predicted less impairment. Increased age was a weak predictor (beta = 0.178; p = 0.001) of disability. With a p of 0.062 the radiological severity according to the grading of Kellgren and Lawrence slightly surpassed the required significance level for remaining in the final regression model. CONCLUSION: The results emphasize that psychological as well as physical factors need to be addressed similarly to improve functional ability of patients suffering from OA. More research with multifaceted and tailored interventions is needed to determine how these factors can be targeted appropriately.